2014
DOI: 10.1159/000357794
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Severity of Semantic Deficits in a Consecutive Memory Clinic Cohort

Abstract: Background/Aim: Semantic memory deficits have been shown in dementia and mild cognitive impairment (MCI) by group comparisons. The aim of this study is to investigate the frequency of impairments on tests with semantic content in patients with dementia, MCI (amnestic and non-amnestic) and affective disorders. Methods: A Famous faces test, Boston Naming Test and Category fluency were applied in 114 consecutive memory clinic patients and 95 healthy participants (all participants were 60 years old or older; demen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
4
5
1
Order By: Relevance
“…We found that although the two MCI groups did not significantly differ in the category fluency impairment, this impairment was more pronounced in the naMCI group compared to the aMCI group. Our finding is consistent with some previous reports of slightly better category fluency performance in (single-domain) aMCI compared to non-amnestic or dysexecutive MCI (Brandt and Manning, 2009 ; Libon et al, 2010 ; Vogel et al, 2014 ). However, our finding is not consistent with other findings of slightly better category fluency performance in naMCI than aMCI (Weakley et al, 2013 ; Rinehardt et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that although the two MCI groups did not significantly differ in the category fluency impairment, this impairment was more pronounced in the naMCI group compared to the aMCI group. Our finding is consistent with some previous reports of slightly better category fluency performance in (single-domain) aMCI compared to non-amnestic or dysexecutive MCI (Brandt and Manning, 2009 ; Libon et al, 2010 ; Vogel et al, 2014 ). However, our finding is not consistent with other findings of slightly better category fluency performance in naMCI than aMCI (Weakley et al, 2013 ; Rinehardt et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our behavioral findings are consistent with previous findings of word generation deficits in individuals with MCI (Nutter-Upham et al, 2008 ; Brandt and Manning, 2009 ; Murphy et al, 2006 ; Libon et al, 2010 ; Wang et al, 2011 ; Price et al, 2012 ; Bertola et al, 2014 ; Rinehardt et al, 2014 ; Vogel et al, 2014 ; Weakley et al, 2013 ), suggesting that impaired retrieval of semantic knowledge may already be observed at the earliest stage of transition between normal aging and dementia. Moreover, we found that individuals with MCI generated fewer animal subcategories and make fewer switches between subcategories.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Identification of famous faces was reported to be impaired in 14% of predementia AD patients and 39% in AD patients in an earlier study (Vogel et al, 2005). In a subsequent study of the same group identification of famous faces was reported to be impaired in 33% of naMCI patients, in 43% of aMCI patients, and 43% of AD patients, respectively (Vogel et al, 2014). These numbers are similar to the present results.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have shown that semantic memory is affected by the presence of depressive symptoms. [10][11][12] Brunet et al 10 conducted a study to verify the relationship between depressive symptoms and semantic memory in elderly people with mild cognitive impairment-amnestic (MCIa) and depression. The results showed that depressive symptoms modulate the presentation of semantic memory deficits in people with MCIa.…”
Section: Introductionmentioning
confidence: 99%